Effect of SVPWM vector synthesis methods on the DC bus charge station leakage current - Zhou, Xin-Yu; Jiang, Jiu-Chun; Zhang, Gang; Zhang, Wei-Ge; Bao, Yan (Dianli Xitong Baohu yu Kongzhi, 2013)
In order to reduce costs and loss, the electric vehicle charging station with the DC bus topology does not add the isolation transformer, and produces leakage current. Based on a theoretical analysis of the reason of producing leakage current, a common mode leakage current model of transformerless DC bus charging station is proposed. Based on this model and the theory of SVPWM converter, the mathematical descriptions of common mode voltage and leakage current are given. The effect of different space vector synthesis modes on the common mode voltage and leakage current of charging station system is analyzed when the grid-connected inverter uses SVPWM control. The common mode voltage and current of different space vector synthesis modes are obtained. Experiments and simulation verify the correctness of the modeling method and space vector synthesis theory.